Agreement and reliability between the two-day 6-minute incremental step test and two-day cardiopulmonary exercise test in post COVID-19 condition for assessing post-exertional malaise: The REVEAL-study - Sarah Bomans; Naomi Michotte; Imane El M’Rabet; Berenice Jimenez Garcia; Lynn Leemans; Peter Janssens; Shane Hanon; Elisabeth De Waele; David Beckwée (PLoS ONE, 2026)
Background Post-Exertional Malaise (PEM) is a core symptom of post COVID-19 condition (also known as long COVID) affecting millions of people, yet assessment remains challenging. The two-day cardiopulmonary exercise test (CPET) is the current gold standard for objectifying PEM, but its cost and patient burden limit use. The two-day 6-minute incremental step test (6MIST) with wireless wearable sensors could offer a more accessible alternative. Methods This cross-over study (n = 25, one-month washout period) evaluated the level of agreement and reliability between the two-day 6MIST and the two-day CPET for assessing PEM. Each “two-day” test consisted of two identical exercise tests separated by 24 hours to capture worsening of symptoms on day 2. Objective (VO 2 peak) and subjective (fatigue, neuromuscular complaints and rated perceived exertion) PEM outcomes were collected. Subjective outcomes were measured in relation to the first exercise test of each two-day session; at 15 minutes pretest, 15 minutes posttest and 24 hours posttest, with changes analyzed as Δ1 (baseline to 15 minutes posttest) and Δ2 (15 minutes posttest to 24 hours posttest). Agreement was assessed using Bland-Altman plots and reliability through consistency Intraclass Correlation Coefficients. The study is registered in ClinicalTrials.gov (Ref: NCT06933017). Results VO 2 peak and neuromuscular complaints showed low agreement and reliability between the two tests. Rated perceived exertion showed moderate reliability at all times and fatigue showed moderate reliability for changes after 24h (Δ2). Conclusions Contrary to our hypothesis, the two-day 6MIST shows limited agreement with the two-day CPET overall. However, moderate reliability for rated perceived exertion and fatigue suggests potential for improvement with protocol refinement. Further research is needed to optimize the two-day 6MIST and to develop assessments that capture PEM both within and beyond the 24-hour period.